A case of recurrent congenital fetal anomalies associated with a familial subtelomeric translocation. - Brackley, K; Kilby, MD; Morton, J; Whittle, M; Knight, S; Flint, J (1999)
The potential of a new fluorescent in situ hybridization technique is discussed, which uses a complete set of telomeric probes to reveal cryptic chromosome rearrangements that remain undetected by standard cytogenetic analysis. We report the obstetric history of a patient who had a termination of pregnancy at 20 weeks for a fetus with multiple congenital anomalies but a normal male karyotype using conventional G-banding analysis on a mid-trimester placental biopsy. In a subsequent pregnancy, a diaphragmatic hernia and intra-uterine growth restriction were detected at 34 weeks' gestation and a fetal blood sample showed a normal female karotype. However, her child was born with dysmorphic features and additional severe abnormalities including microcephaly, anophthalmos and left fixed talipes. The child has shown marked developmental delay. In view of a strong family history of congenital abnormalities and recurrent miscarriage suggestive of a familial translocation, a fluorescent in situ hybridization technique using specific telomeric probes was performed on blood from the affected child and her parents. An unbalanced subtelomeric translocation was detected involving the long arms of chromosomes 2 and 7 in the child and a balanced translocation was detected in her father. Accurate genetic counselling and the opportunity for early prenatal diagnosis can now be offered to this family.